Durorp-English Dictionary - Inyang, Ekpe (Book collections on Project MUSE., 2013)
Durorp-English Dictionary is probably the first attempt at compiling a comprehensive Dictionary of Durorp, the language of the people of Korup. It is a bilingual Dictionary aimed at stimulating literary interests in the study and development of Durorp as a linguistic entity in particular and promotion of Durorp literature in general. Durorp is an interesting and linguistically distinct semi-Bantu or Bantoid language spoken by a minority group of people known as Bororp or people of the Kororp ethnic group. A part of this ethnic group inhabits the Southwestern part of Cameroon while the other occupies the Southeastern tip of Nigeria. A minority group, Kororp has continued to suffer not only cultural and socio-economic shrinkage but also linguistic marginalisation characterised by an obvious erosion of some key elements of the language. Like any other language, however, Durorp has borrowings from languages such as Efik, Ejagham, and even English. This Dictionary has introduced quite a number of new but understandable words.